2009
DOI: 10.1111/j.1365-2133.2008.08942.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing squamous cell carcinomas: audit on the mode of referral and adequacy of surgical excision

Abstract: vehicle containing propylene glycol, and the area treated became excoriated. After recovery to baseline renal function, cidofovir 1% gel once daily was started with excellent response and no side-effects. 10 No studies have been performed to investigate the bioavailability of topical or intralesional cidofovir in humans. 8 Rabbit studies suggest that propylene glycol, abrasion and occlusion increase skin absorption. 11 We did not monitor renal function in our patients, as blood tests are considered more in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…Regarding margin involvement by tumour in excision biopsies, it is alarming that such a high percentage of those procedures carried out by GPs fell into this category. Our findings have been reproduced by other studies investigating excision biopsies of melanoma, 14,15 BCC 16–21 and SCC, 21,22 with incomplete excisions more commonly attributed to GPs than secondary care providers in each study. Incomplete excision rates are also high among plastic and other surgical specialities in our study, but this is likely to be largely explicable in terms of the more complex caseload taken on by these surgeons, with larger tumours tackled in more challenging anatomical locations.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarding margin involvement by tumour in excision biopsies, it is alarming that such a high percentage of those procedures carried out by GPs fell into this category. Our findings have been reproduced by other studies investigating excision biopsies of melanoma, 14,15 BCC 16–21 and SCC, 21,22 with incomplete excisions more commonly attributed to GPs than secondary care providers in each study. Incomplete excision rates are also high among plastic and other surgical specialities in our study, but this is likely to be largely explicable in terms of the more complex caseload taken on by these surgeons, with larger tumours tackled in more challenging anatomical locations.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, it is of concern that a significant proportion of cases operated on by GPs should instead have been managed surgically in secondary care according to current NICE guidance for skin cancer. Several recent U.K. studies investigating dermatological surgical practice in primary and secondary care have highlighted this issue 22–26 . It has been suggested that patients may be exposed to unnecessary risk as a result, either through receiving inappropriate or inadequate treatment for their skin cancer, or being subjected to a delay in accessing definitive treatment 22,24,25 …”
Section: Discussionmentioning
confidence: 99%
“…Overall, incomplete excision rates in this audit for both BCC and SCC were 3%. This is low compared with previously published data, which has suggested incomplete excision rates of 7.5–16% for dermatologists, and is comparable to previous data for plastic surgeons (4–13%) . Incomplete excision rates in primary care and in other nonspecialist settings appear to be very variable, reported at between 1.6 and 43% .…”
Section: Discussionsupporting
confidence: 58%
“…Incomplete excision rates for cutaneous SCC in the literature range from 5% to 17.6% . Incomplete excisions frequently occur with cutaneous SCC of the head and neck and tend to occur at the deep margin of the excision .…”
Section: High‐risk Factors In Cutaneous Squamous Cell Carcinomamentioning
confidence: 99%